Periprosthetic joint infection with Ureaplasma parvum detected by 16S rRNA PCR - Ball, Nicola Diane (BMJ Case Rep, 2021)
Usual culture methods to identify pathogenic bacteria can be unsuccessful, particularly when working with fastidious organisms. We present a case of early periprosthetic knee joint infection with Ureaplasma parvum only identified using 16S ribosomal RNA PCR. This case represents the impact molecular methods of bacterial identification can have on clinical care allowing for more targeted antimicrobial therapy; something which is imperative in an era of increasing antimicrobial resistance.